Podnebne spremembe, poplavna varnost in vodooskrba v Sloveniji - Bizjak, Aleš (Urbani izziv, 1999)
The forecast following research on climatic changes and consequences of global warming on the environment that were carried out by research institutes predict qualitative and quantitative changes in certain elements of the water cycle, such as: precipitation, soil humidity, storms and intensive weather and the sea level. The article shows possible effects of climatic change on the water cycle, floods and water supply in Slovenia.
Keywords: climate; klimatske spremembe; oskrba z vodo; padavine; podnebje; poplave; Slovenia; Slovenija